IoT-Based Automatic Watering and Flow Detection System via Telegram - Ketut Gde Manik Karvana; Ni Ketut Utami Nilawati; Evi Dwi Krisna (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
Gardens are an important part of the surrounding environment, so they need to be maintained regularly. Manual watering systems are often inefficient. An automatic watering system based on the ESP 8266 was created which offers a more efficient solution, and plants get an adequate water supply. The system will water the plants according to the schedule that has been designed. This system is also equipped with a no-water flow detector to prevent plants from being watered during the watering schedule, and will provide a warning if there is no water flow. This warning is then sent via Telegram Messenger. Of the 20 tests of the automatic watering system, the watering start notification was sent successfully 17 times (80%), while the watering stop notification was successfully sent 18 times (90%). The main obstacle occurs on normal lecture days. Checking via the Wireshark application proved that there were several very high packet loss values (2.8514), which indicates that many data packets were lost during transmission. The water flow meter sensor only detected no water flow on one occasion out of 20 tests. This research shows that an automatic watering system and detection of no water flow can make the work of INSTIKI employees easier.